2010
DOI: 10.1096/fj.10-166595
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fat decreases intestinal levels of the anorectic lipids through a fat sensor

Abstract: This study was undertaken to investigate the link between dietary fat content and intestinal levels of anorectic N-acylethanolamines (NAEs), including oleoylethanolamide (OEA), palmitoylethanolamide (PEA), and linoleoylethanolamide (LEA). Male rats were fed high-fat diets (HFDs) with variable percentages of fat [20-45% of total energy (E%)] for 1-7 d; afterward, the jejunums were isolated, and jejunal NAE levels were measured by liquid-chromatography mass spectrometry. Enzyme activities and mRNA expression lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
103
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(115 citation statements)
references
References 53 publications
(81 reference statements)
9
103
3
Order By: Relevance
“…For instance, it has been observed that plasma and tissue levels of NAEs in hamsters are modifi ed in response to dietary fatty acid composition and are observed to specifi cally activate lipid metabolism pathways through NAE-regulated mechanisms ( 5 ). Although it has been demonstrated that overall high-fat feeding modulates circulating and peripheral NAE levels irrespective of their fatty acid composition ( 20,21 ), the present human study shows that different dietary fatty acid compositions are capable of altering plasma NAE content in a compositiondependent manner, irrespective of the isoenergetic high-fat content (34% energy), which is consistent with previous animal studies examining this question ( 5,13 ). In fact, the plasma NAE levels were observed to shift solely in response to the type of fatty acid, rather than the quantity of overall dietary fat, suggesting that NAE levels can be signifi cantly modulated through dietary fat choice.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it has been observed that plasma and tissue levels of NAEs in hamsters are modifi ed in response to dietary fatty acid composition and are observed to specifi cally activate lipid metabolism pathways through NAE-regulated mechanisms ( 5 ). Although it has been demonstrated that overall high-fat feeding modulates circulating and peripheral NAE levels irrespective of their fatty acid composition ( 20,21 ), the present human study shows that different dietary fatty acid compositions are capable of altering plasma NAE content in a compositiondependent manner, irrespective of the isoenergetic high-fat content (34% energy), which is consistent with previous animal studies examining this question ( 5,13 ). In fact, the plasma NAE levels were observed to shift solely in response to the type of fatty acid, rather than the quantity of overall dietary fat, suggesting that NAE levels can be signifi cantly modulated through dietary fat choice.…”
Section: Discussionmentioning
confidence: 99%
“…The only clinical study performed did not fi nd an anorectic effect of OEA, but the dietary supplement used was phosphatidylethanolamine given as a parent OEA metabolic precursor ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…As seen with gut peptide hormones such as GLP1 (122,123), continued exposure to a high-fat diet lowers OEA levels in the small intestine of rodents (112,124,125). Does this effect influence OEA-mediated satiety signaling?…”
Section: Lipid-derived Signals Of Satietymentioning
confidence: 99%
“…This response also depends on the presence of an intact sympathetic nervous system -which may function to facilitate fat-induced OEA production in the gut -and engages oxytocin, histamine, and dopamine transmission in the CNS. The intriguing but as yet unexplained observation that prolonged exposure to dietary fat lowers small intestinal OEA levels (124,125) raises questions about the mechanism regulating OEA signaling in the gut and the possible role it might play in overeating and obesity. glycerols by pancreatic lipase is capable of eliciting a similar effect.…”
Section: Lipid-derived Signals Of Satietymentioning
confidence: 99%